Pembuatan Komik Digital Sebagai Sarana Promosi Wisata Sejarah Candi Palgading di Desa Wisata Palgading, Kecamatan Ngaglik, Kabupaten Sleman - Fatimah, Atika (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2024)
Digital Comic Creation As A Means Of Promoting Historical Tourism of Palgading Temple in Palgading Tourism Village, Ngaglik District, Sleman Regency Palgading Tourism Village which is located on Jalan Kaliurang KM 9, Palgading Hamlet, Sinduharjo Village, Ngaglik District, Sleman Regency, has several business units in the tourism sector are camping ground, riverside and Palgading Temple, but currently it is in a vacuum or economically unproductive due to land acquisition problem. Therefore, the purpose of this community service is to raise historical tourism in the Palgading Tourism Village namely the Palgading Temple site which is a relic of the VII-X century AD where Hindu-Buddhist religion was growing rapidly at that time through making digital comics about the history of Palgading Temple. The method for implementing community service activities consists of several stages of making digital comics, including research, writing comic scripts, sketching, inking, coloring and finishing. The result is that a digital comic has been made which consist of 10 panels. The existence of a digital comic tells the story of the Palgading Temple has an impact on the history of tourism for Palgading Tourism Village.